Mutu dan Profil Asam Lemak Minyak Kelapa dari Penggunaan Inokulum Tempe pada Tahap Ekstraksi - Karseno, Karseno; Syifa, Khumairoh Asy; Haryanti, Pepita (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Coconut oil is one of the popular vegetable oils and the product is made through physical, chemical, and enzymatic extraction of coconut flesh. In this study, coconut oil was obtained by physical and enzymatic procedure. The purpose of this study was to determine the effect of physical extraction time (5, 10, and 15 min) and tempe inoculum concentration (1, 3, and 5% w/v) on the quality and fatty acid profiles of the coconut oil. Sample analyses included peroxide, free fatty acids, moisture, viscosity, total insoluble solids, and fatty acid profile of the selected sample. The results showed that both treatments showed a considerable impact on the quality of coconut oil. The extraction time of 15 min and a tempe inoculum concentration of 1% yielded the most desirable coconut oil, with peroxide levels of 1 meq/kg, free fatty acid levels of 0.12%, a moisture content of 16%, and a viscosity of 47.70 mPa.s. In terms of fatty acids, it contains 0.50% caproic acid, 8.42% caprylic acid, 7.53% decanoic acid, 39.01% lauric acid, 18.83% myristic acid, 10.70% palmitic acid, 11.99% oleic acid, 2.76% linoleic acid, 0.13% gondoic acid, and 0.14% pentadecanoic acid. Considering its components, it is found that they comply with the standard of SNI 2902-2011. Moreover, GC-MS data revealed the very first reported fatty acid in coconut oil, which is pentadecanoic acid. The lowest peroxide value was 1 mg ek/kg, obtained at extraction time of 15 min. With the presence of pentadecanoic acid and low peroxide value, the coconut oil is much more stable against oxidation, opening broader industrial uses including soap, detergent, cosmetics and other chemical products.